1999
DOI: 10.1046/j.1439-0434.1999.147001041.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variability in Colletotrichum lindemuthianum and Evaluation of Resistance in Phaseolus vulgaris in the North‐Western Himalayan Region of India

Abstract: Eightyfive isolates of Colletotrichum lindemuthianum (bean anthracnose) collected from different kidney bean growing areas of a hilly state (Himachal Pradesh) of India, were characterized on the basis of their reaction types on International and CIAT differentials. On international differentials, 12 races viz., Alpha‐Brazil, Beta, Gamma and Ind I to Ind IX were characterized. The races designated as Ind I to Ind IX were different from those identified in Europe and USA, thus forming a new race group from the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Extensive discussion on the breeding value of both genes is available (Kelly and Vallejo 2004). Previous works have shown that PI 207262 possesses a narrower anthracnose resistance spectrum than TO (Co-4) and SEL 1308 (Co-4 2 ) (Araya et al 1991;Balardin et al 1999;Sharma et al 1999). This weaker resistance pattern in PI 207262 which carries two resistance genes, compared with other sources of the Co-4 gene (TO and SEL 1308), suggests that PI 207262 carries a different allele at the Co-4 locus which conditions resistance to fewer C. lindemuthianum races.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive discussion on the breeding value of both genes is available (Kelly and Vallejo 2004). Previous works have shown that PI 207262 possesses a narrower anthracnose resistance spectrum than TO (Co-4) and SEL 1308 (Co-4 2 ) (Araya et al 1991;Balardin et al 1999;Sharma et al 1999). This weaker resistance pattern in PI 207262 which carries two resistance genes, compared with other sources of the Co-4 gene (TO and SEL 1308), suggests that PI 207262 carries a different allele at the Co-4 locus which conditions resistance to fewer C. lindemuthianum races.…”
Section: Discussionmentioning
confidence: 99%
“…Although anthracnose disease has significant detrimental effects in Turkey especially in coastal regions where fresh bean cultivation is common, the studies concerning determination of pathogen strains common to Turkey and of varieties resistant to these strains in Turkey have been initiated only recently. A literature review indicates that in other countries where cultivation is common, strains of the common fungi have been identified and the varieties resistant to the identified strains have been developed (Kelly, Hosfield, Varner, Uebersax, Afanador, & Taylor, 1995;Kelly, Hosfield, Varner, Uebersax, Long, & Taylor, 1998;Balardin & Kelly, 1998;Sharma, Kumar, Sharma, Sud, & Yagi, 1999;Kelly, Hosfield, Varner, Uebersax, & Taylor, 2000;Kelly, Hosfield, Varner, Uebersax, & Taylor, 2001; Acosta-Gallegos, Ibarra-Pérez, Rosales-Serna, Cázares-Enríquez, Fernández-Hernandez, Castillo-Rosales, & Kelly, 2001a,b;Miklas, Kelly, & Singh, 2003). In Turkey, where this agent is present and poses risk of spreading, it is crucial to search for sources of resistance against this pathogen, to protect and make use of the present gene sources and to transfer resistance to native varieties by selective breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Best strategy to manage disease is planting resistant cultivars, which is most effective, least expensive and easiest for farmers to adopt. However, high pathogenic variability present in the pathogen population (Pastor-Corrales et al, 1995;Sharma et al, 1999;Mahuku and Riascos, 2004;Sharma et al, 2007;Padder et al, 2007) renders their use ineffective due to continuous breakdown of the resistance mainly in recommended cultivars with good agronomic and marketability traits (Sharma et al, 1994;Kumar et al, 1997).…”
Section: Introductionmentioning
confidence: 99%